2014
DOI: 10.1002/ange.201403754
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Decarboxylative Cycloaddition of Vinylethylene Carbonates with Formaldehyde: Enantioselective Construction of Tertiary Vinylglycols

Abstract: An efficient method for the enantioselective construction of tertiary vinylglycols through a palladium-catalyzed asymmetric decarboxylative cycloaddition of vinylethylene carbonates with formaldehyde was developed. By using a palladium complex generated in situ from [Pd 2 -(dba) 3 ]·CHCl 3 and a phosphoramidite ligand as a catalyst under mild reaction conditions, the process allows conversion of racemic 4-substituted 4-vinyl-1,3-dioxolan-2-ones into the corresponding 1,3-dioxolanes, as methylene acetal protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(3 citation statements)
references
References 52 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…225 Their approach utilizes racemic vinyl-substituted ethylene carbonates as substrates that undergo CO 2 extrusion upon exposure to catalytic Pd 2 (dba) 3 ·CHCl 3 and ( S , S , S )-phosphoramidite 174 (Figure 20), leading to a rapidly interconverting dynamic system comprising of diastereomeric π-allylpalladium intermediates. Formaldehyde then reversibly captures the Pd-alkoxide intermediate, generating a new pair of diastereomeric Pd-allyl complexes, which is much slower to equilibrate.…”
Section: Dynamic Kinetic Asymmetric Transformationsmentioning
confidence: 99%
“…225 Their approach utilizes racemic vinyl-substituted ethylene carbonates as substrates that undergo CO 2 extrusion upon exposure to catalytic Pd 2 (dba) 3 ·CHCl 3 and ( S , S , S )-phosphoramidite 174 (Figure 20), leading to a rapidly interconverting dynamic system comprising of diastereomeric π-allylpalladium intermediates. Formaldehyde then reversibly captures the Pd-alkoxide intermediate, generating a new pair of diastereomeric Pd-allyl complexes, which is much slower to equilibrate.…”
Section: Dynamic Kinetic Asymmetric Transformationsmentioning
confidence: 99%
“…[6] Recently,P d-catalyzed efficient decarboxylative transformations of vinylethylene carbonates (VCCs) with various electrophiles and (pro)nucleophiles have been reported. [7][8][9][10] In this context, Kleij, Maseras and co-workers developed aP d-catalyzed allylic substitution of VCCs 1 with aryl-and alkyl-amines (Scheme 1c). [8] Notably,w ith the diphosphine ligand L1,c omplete linear regioselectivity and high (Z)stereoselectivity was observed, thus providing ag eneral method for the stereoselective construction of tri-and tetrasubstituted allylic amines (Z)-2.Adetailed reaction mechanism was also provided by DFT calculations,a nd the computational results showed that the reaction follows ag enerally accepted outer-sphere pathway in line with the experimental results.A talater stage,K leij and co-workers found that the regioselectivity of this reaction can be switched towards the branched product through ligand control.…”
Section: Introductionmentioning
confidence: 99%
“…Formaldehyde could also be used efficiently in the decarboxylative [3+2] cycloaddition with VECs 215 to form 1,3‐dioxolanes 243 with excellent enantioselectivities using the chiral phosphoramidite ligand 239 . The methylene acetal‐protected tertiary vinylglycol products 243 are useful chiral precursors for natural products as they can be readily deprotected, forming the corresponding tertiary vinylglycols without erosion of enantioselectivity (Scheme A).…”
Section: Pd‐catalyzed Interceptive Decarboxylative Asymmetric Allylicmentioning
confidence: 99%